2020 IEEE Winter Conference on Applications of Computer Vision (WACV) 2020
DOI: 10.1109/wacv45572.2020.9093339
|View full text |Cite
|
Sign up to set email alerts
|

The Synthinel-1 dataset: a collection of high resolution synthetic overhead imagery for building segmentation

Abstract: Recently deep learningnamely convolutional neural networks (CNNs)have yielded impressive performance for the task of building segmentation on large overhead (e.g., satellite) imagery benchmarks. However, these benchmark datasets only capture a small fraction of the variability present in real-world overhead imagery, limiting the ability to properly train, or evaluate, models for real-world application. Unfortunately, developing a dataset that captures even a small fraction of real-world variability is typicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…However, their world is lifeless and does not feature any objects of interest. The Synthinel-1 [34] data set features synthetic data showing building footprints with segmentation masks.…”
Section: A Related Workmentioning
confidence: 99%
“…However, their world is lifeless and does not feature any objects of interest. The Synthinel-1 [34] data set features synthetic data showing building footprints with segmentation masks.…”
Section: A Related Workmentioning
confidence: 99%
“…Within the last few years, there has been some research that has focused on applications of synthetic data in aerial imagery. For example: Bondi et al [46] used the AirSim tool to generate BIRDSAI, an infrared object recognition dataset that blends both real and synthetic data; Chen et al [47] published VALID, a synthetic dataset for instance segmentation, semantic segmentation, and panoramic segmentation from an unmanned aircraft perspective; Kong et al [48] investigated the application of synthetic data to semantic segmentation for remote sensing and published the Synthinel-1 dataset; Shermeyer et al [49] released RarePlanes, a hybrid real-and synthetic-image dataset for aircraft detection and fine-grained attribute recognition in aerial imagery; Clement et al [50] also released a synthetic image dataset for aircraft recognition, and this is mainly intended for rotated object recognition; Lopez-Campos et al [51] released ESPADA, the first synthetic dataset for depth estimation in aerial images; Uddin et al [52] proposed a method for converting optical videos to infrared videos using GAN, investigating the impact for classification and detection task.…”
Section: Synthetic Aerial Image Datasetsmentioning
confidence: 99%
“…One emergent limitation of DNNs in remote sensing however is their sensitivity to the statistics of their training imagery. Recent research has shown that DNNs often perform unpredictably, and often much more poorly, when they are applied to novel collections of imagery, which were not present in their training data [31,19,22,14]. Furthermore, this performance degradation seems to occur even if DNNs are trained on relatively large and diverse datasets, encompassing large and diverse geographic regions [19,14].…”
Section: Introductionmentioning
confidence: 99%
“…The performance degradation of DNNs on new sets of imagery are caused by visual domain shift (a.k.a. distribution shift): statistical differences between the training imagery and new collections of imagery [31,19]. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation